Theranostic applications of multifunctional carbon nanomaterials. Issue 2 (3rd March 2023) - Masoudi Asil, Shima; Guerrero, Erick Damian; Bugarini, Georgina; Cayme, Joshua; De Avila, Nydia; Garcia, Jaime; Hernandez, Adrian; Mecado, Julia; Madero, Yazeneth; Moncayo, Frida; Olmos, Rosario; Perches, David; et al.
Abstract: Nanobiotechnology is one of the leading research areas in biomedical science, developing rapidly worldwide. Among various types of nanoparticles, carbon nanomaterials (CNMs) have attracted a great deal of attention from the scientific community, especially with respect to their prospective application in the field of disease diagnosis and therapy. The unique features of these nanomaterials, including favorable size, high surface area, and electrical, structural, optical, and chemical properties, have provided an excellent opportunity for their utilization in theranostic systems. Carbon nanotubes, carbon quantum dots, graphene, and fullerene are the most employed CNMs in biomedical fields. They have been considered safe and efficient for non‐invasive diagnostic techniques such as fluorescence imaging, magnetic resonance imaging, and biosensors. Various functionalized CNMs exhibit a great capacity to improve cell targeting of anticancer drugs. Due to their thermal properties, they have been extensively used in cancer photothermal and photodynamic therapy assisted by laser irradiation and CNMs. CNMs also can cross the blood‐brain barrier and have the potential to treat various brain disorders, for instance, neurodegenerative diseases, by removing amyloid fibrils. This review has summarized and emphasized on biomedical application of CNMs and their recent advances in diagnosis and therapy. Abstract : Carbon nanomaterials are potent multifunctional materials with diverse biomedical applications in theranostic techniques such as biosensing and bioimaging, treatment of cancer, brain disorders, and cardiovascular diseases.